MAPPING FIRE HAZARD LEVEL IN BUKITTINGGI CITY - Feri Ferdian; Arie Yulfa (JURNAL BUANA, 2022)
Abstract This study aims to (1)To find out the threat level of fire disasters in Bukittinggi City (2) To map the distribution of areas that have a fire threat level in Bukittinggi City (3) To find out the factors that cause fires in Bukitttinggi City. Research method used is quantitative descriptive research. Data collection techniques in this study are by means of observation, interview and literature studies. Data analysis techniques that are used is scoring analysis, the result of this study is (1) The fire threat level in Bukittinggi City is divided into 3 classes, namely High, Medium and Low threat classes. (2) Spread of fire threat level in Bukittinggi City there are 2 subdistricts with the number of 9 villages that are at a high threat level and 3 subdistricts with the number of 9 villages that are at medium threat level and 2 subdistricts with a total of 6 subdistricts at low threat level (3) For the fire cause factor itself there are 3 factors causing fires, namely short circuit of listic currents , gas and stove leaks and public negligence Keywords : Mapping, Disaster, Fire